***NOTICE OF RETRACTION*** An Analysis of Mobile Dictionaries in Vocabulary Teaching - Masykur Masykur (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
This paper is retracted by Academic Journal Perspective: Education, Language, and Literature Universitas Swadaya Gunung Jati (UGJ). The publisher has discovered that the author, Masykur, from Universitas Wiralodra, whose paper entitled An Analysis of Mobile Dictionaries in Vocabulary Teaching Vol 5, No 1, pp. 29-35, Mei 2017, DOI: http://dx.doi.org/10.33603/perspective.v5i1.543 violates the caution of copyright and allegedly infringed work and copying the work of Erdinc Aslan without permission, which entitled A Study on the Use of Mobile Dictionaries in Vocabulary Teaching published in Journal of Language and Linguistic Studies in Vol 12, No 1 (2016) http://www.jlls.org/index.php/jlls/article/view/463.We take seriously the value of intellectual property, thus, as the consequences of his allegations, the document and its content has been removed from Academic Journal Perspective: Education, Language, and Literature and reasonable effort should be made to remove all references to this article.